Trajectory Tracking and Disturbance Rejection Performance Analysis of Classical and Advanced Controllers for a Scorbot Robot - Urrea-Onate, E; Kern-Molina, J; Becker-Cares, C; Verdejo-Fredes, H; Agramonte-Alburquerque, R (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This work presents the design and assessment of four control schemes for the monitoring and regulation of joint trajectories applied in the dynamic model of a SCORBOT-ER V plus robot, which includes the dynamics of the actuators, and the estimation of the friction forces present within the joints. The two classical control strategies calculated torque and PID, and the two advanced control strategies, fuzzy and predictive, are considered. In the latter case, a gravitational compensation stage is incorporated, as well as the inverse models of the motors and the transmissions of belt movement for each joint. Computational tests are performed by applying an external step-type disturbance to the third joint of the robot. Finally, an evaluation of the results obtained is presented through trajectory curves, joint errors, and the three performance indexes residual mean square, residual standard deviation, and index of agreement. © 2024 by the authors.